Basaloid squamous cell carcinoma of the maxilla. (8th June 2015) - Pathak, Jigna; Patel, Shilpa; Iyer, Janaki Subramanian; Mohanty, Neeta
Abstract : Basaloid squamous cell carcinoma (BSCC) is a distinctive aggressive variant of squamous cell carcinoma. We present a case of a 60-year-old man with tender swelling in the right cheek region for 6 months and continuous unilateral nasal discharge for 2 months. Extraoral examination revealed an ovoid, well-defined swelling from the right infraorbital rim to the angle of the mouth superoinferiorly and the right lateral wall of the nose to preauricular region anteroposteriorly. Intraorally, an ulceroproliferative growth from right upper gingivobuccal sulcus to mid palatine raphe with bicortical expansion was evident. CT revealed a hypodense mass obliterating the right maxillary sinus. Histopathology showed closely packed basaloid cells, with hyperchromatic palisading nuclei, arranged in a solid pattern with a lobular configuration. Prominent areas of comedo necrosis and keratin pearl formation were seen. These features suggested BSCC. The patient underwent surgical excision with adjuvant radiation but was lost to follow-up after 6 months of radiation therapy.